Green building financing - Brunko, Pavlo (Skhid, 2016)
The article is devoted to the problem of green buildings financing. It is noted that bank lending can be a major source of funds for construction. However, current trends in the economy of Ukraine shows that credit, especially lending to construction, is in poor condition. Accordingly, there is a need to explore the possibility of additional measures that can be applied to bringing financial resources into the construction. The author brings evidence in favor of feasibility of raising funds for construction in the form of investment loans. For investment loans, the most important feature is specifications of the particular project that is an object of an investment. In evaluating the appropriateness of investment UNIDO methodology is applied. It takes into account both quantitative and qualitative indicators. Comparison of conventional and energy-efficient construction project financing is presented in the article. The comparison takes into account a number of indicators that demonstrate that energy-efficient construction has several advantages in terms of investment attractiveness. Comprehensive analysis shows that these investment projects have higher net present value, the best indicators of the criterion Bruno as well as commercial, institutional, environmental and social criteria. The disadvantages include a certain uncertainty that is caused by the unclear future cost of energy, but to some extent, that is offset by the positive impact of numerous macroeconomic factors. The author cites studies conducted by many scientists, who argue that energy-efficient buildings are somewhat supreme in construction costs, but create competitive advantages, reflected in the reduction of operating costs, increase in the size of rent payments and total returns.